Clinical Outcomes Improvement and Perioperative Management of Surgical Patients (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
The art and science of clinical outcome analysis, quality improvement, the perioperative management of surgical patients, and patient safety continue to evolve at an increasingly rapid pace. In fact, over the years, novel concepts have arisen (risk stratification, shared decision-making, interdisciplinary meetings, prehabilitation, etc.), new initiatives have taken shape (e.g., state/nation-wide or international clinical databases), and new technologies and methods have been adopted across all surgical specialties (e.g., minimally invasive or robotic approaches). In order to care for our patients, raise the standards of healthcare services, and be successful in today’s and tomorrow’s rapidly changing healthcare environment, understanding and developing these topics represents an essential duty of all surgeons, physicians, and professionals in relation to the care of surgical patients. In the present Special Issue, we provide the best currently available evidence on several aspects of this important topic, thus providing all of the necessary information to clinicians on core concepts in the perioperative management of surgical patients.